Keputusan Pengusaha Dalam Pengambilan Laba Pada Usaha Mikrokecil Dan Menengah Pembuatan Krupuk Samiler Di Warga Dusun Ketanen Desa Kemasantani Rt.3 Rw.1 Kecamatan Gondang Kabupaten Mojokerto - Imam Baidlowi Baidlowi (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2021)
Micro, Small and Medium Enterprises (MSMEs) are one of the industries that contribute to advancing the economy in Indonesia. With the large number of MSMEs, the competition will be increasingly fierce. In manufacturing companies, cost information can be seen in the calculation of the cost of goods manufactured. The calculation of the cost of goods manufactured can be used to determine the selling price and profit. And the research was conducted in Ketanen hamlet, Kemasantani village RT.3 RW.1 Ketanen, Gondang District, Mojokerto Regency. The purpose of this study is to determine the calculation of the cost of production using the entrepreneur to calculate profit. . This type of research is a descriptive study with a quantitative approach. The results showed that the company had not calculated the cost of goods manufactured correctly and the contribution margin for Samiler crackers per kilo gram was Rp. 4,416.77 has not been deducted by fixed costs. The contribution margin is not a net profit from product sales, because there are fixed costs that must be paid or closed by the company with this margin value. And if it is reduced by fixed costs of Rp. 3,470.58, the profit will be Rp. 946.19. The results of the analysis indicate that the calculation of the cost of goods manufactured using the calculation of the cost of goods is accurate, so that the company has not been able to use this as a basis for determining the cost of goods sold and making decisions to determine profit.